Implementasi Peran Kepolisian Resor Kupang Kota Dan Faktor-Faktor Penghambat Terhadap Penanggulangan Tindak Pidana Perjudian Bola Guling Dalam Masa Kabung Kematian Di Masyarakat Kota Kupang - Yohanes Justhen Raynaldo; Rudepel Petrus Leo; Heryanto Amalo (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to analyze the implementation of the role of the Kupang City Resort Police and the inhibiting factors against overcoming the criminal act of rolling ball gambling in the period of death in the Kupang City community. This research is a type of empirical legal research where the data is obtained directly from the research location. This research uses interview guidelines for 6 narrators. The data was analyzed descriptively. This research was conducted with the method used in collecting data, namely interviews and documentation studies. The data collected was then analyzed and then presented or presented descriptively qualitative. The results showed that: (1) The police policy in eradicating Bola Guling gambling at the Kupang City Police Station using the gambling countermeasure programme is still running independently without centralized coordination between the police and other government agencies. In addition, it is carried out by the Kupang City Resort Police through two efforts, namely preventive and repressive approaches (2) The inhibiting factors in overcoming the crime of Bola Guling gambling in the period of Kabung residents at Kupang City Police can be seen in terms of laws, law enforcement officials, and legal culture.